KONSEP FRAME ALIGNMENT PROCESSES DALAM GERAKAN MAHASISWA ISLAM: STUDI KASUS PADA KAMMI (KESATUAN AKSI MAHASISWA MUSLIM INDONESIA) - Pratiwi, Arundina (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
This paper aims to provide an empirical understanding of frame alignment processes in a contemporary Indonesian Islamic social movement organization (SMO). Field research on KAMMI a Muslim students? organization provides the primary empirical foundation for investigating three frame alignment processes: (1) frame amplification; (2) frame transformation; and (3) frame extension. Discussion about KAMMI?s framing processes provides empirical evidences about how KAMMI formulates its strategies to maintain its members and mobilize its potential participants. Additionally, this paper reveals the activists? perspectives on the tendency toward the Islamization of Indonesian society. KAMMI can be classified as a mixture of religious and political movement, with its main goal being to overcome Indonesia?s crises. In particular, moral degradation has beenblamed by KAMMI activists as the main source of various socio-political problems. KAMMI activists believe that this can be solved through implementing a dakwah (proselytizing) movement, through which they argue Islamic values would be a suitable vehicle through which to construct a sacred society. In KAMMI, the activists use and implement the Islamic values under the umbrellaof Islamic revivalism, and characterize their political action as a significant religious duty.